(untitled) (Bangladesh Pharmaceutical Journal, 2017)
In silico studies of the genes of Staphylococcus spp. might establish some correlations with multiple pathological factors. Sixty isolates of Staphylococcus spp. have been studied here targeting virulence and antibiotic resistance genes through in silico tools. Here, in silico PCR (polymerase chain reaction) amplification detected both virulence and antibiotic resistance genes. Study revealed that most of the isolates harboured either cap5 (40%) or cap8 (31.67%) locus gene. Staphylococcal enterotoxin was detected in 63.33% of the isolates. The sea gene, responsible for food poisoning, was detected in 26.67% of the isolates. The tst positive isolates (5%), responsible for toxic shock syndrome, were present in only genotype 8. No exfoliative toxin was detected. The icaA gene, responsible for intracellular adherence, appeared in 80% of the isolates. Alpha hemolysin gene, hla, was detected in 63.33% of the isolates. Sixty-five percent of the isolates harboured the mecA genes. Both ?-lactamase (blaZ) and erythromycin resistance, ermA genes were available in 38.33% of the isolates. In silico pulsed field gel electrophoresis (PFGE) digestion was able to divide isolates into 23 genotypes. Genotype 8 and 11 harboured tetracycline resistance genes, tetM and tetK. The tetM gene (18.33%) was more prevalent than tetK gene (11.67%). Genotype 1 and 11 were considered more virulent than others. Genotype 11 also carried six antibiotic resistance genes but did not carry the genes msrA, msrB, ermB and ermC. The data generated here might aid in the prediction of the virulence and resistance profile based on genotyping as well as contribute in vaccine development. Bangladesh Pharmaceutical Journal 20(1): 71-84, 2017